Reconsideration of the role of hydrogen peroxide in peroxymonocarbonate-based oxidation system for pollutant control - Yang, Zihan; Zhou, Yi; Jiang, Yiqian; Zhao, Peiqing; Meng, Xu (Water research (Oxford), 2025)
•HCO4- was more readily activated to cleave the OO bond.•The primarily role of H2O2 is to form HCO4- rather than its self-decomposition.•The secondary role of H2O2 is to quench generated ·OH and CO3·−.•The altered reaction pathway of H2O2 promotes its utilization efficiency. Advanced oxidation processes that utilize peroxymonocarbonate (HCO4-), generated in-situ through the reaction of HCO3- and H2O2, are employed for the removal of pollutants in water. Nevertheless, the precise role of H2O2 in these processes remains a subject of debate. This study established a HCO4--based oxidation system using NaHCO3 and H2O2 for the degradation of acetaminophen and investigated the activation mechanisms of coexisting oxidants. Under thermal activation conditions, the OO bond in HCO4- (HOOCOO-) was more readily cleaved than the OO bond in the co-existing oxidant H2O2 (HOOH), leading to the generation of reactive oxygen species (ROS). Based on kinetics and ROS evaluation, H2O2 primarily served to form HCO4- rather than converting to ·OH or O2, with HCO4- acting as the primary oxidant for degradation through the formation of CO3·−and ·OH. In this oxidation system, H2O2 utilization efficiency for ·OH production reached 27.34 %, ·OH yield reached 24.15 % and acetaminophen degradation efficiency realized 83 % at 60 °C with 20 mM HCO3- and 20 mM H2O2. The apparent activation energy of acetaminophen degradation and HCO4- activation were calculated as 90.83 kJ mol-1 and 18.81 kJ mol-1, respectively. Moreover, a novel CO2-derived HCO4--based system led to a comparable acetaminophen degradation efficiency of 82 % and a higher kobs of 0.028 min-1. The system optimization and ROS evaluation suggest that high concentration of H2O2 inhibited the degradation and quenched CO3·− and ·OH to yield ·O2- and 1O2. Furthermore, EPR analysis and quenching experiments indicate that CO3·− was mainly responsible for acetaminophen degradation. This work provides fundamental understanding of the HCO4--based oxidation system. [Display omitted]